DNA chromatography - Gjerde, Douglas T. (Wiley-VCH, 2002)
This book describes a powerful and effective tool for the molecular biologist researcher. Readers will discover how DNA chromatography can be used in their own work. Intended as an introduction for the molecular biologist reader, this will also serve as a practical guide for the experienced user. The clear and concise writing style is also attractive to the chemist who wants to learn more about molecular biology.